2019
DOI: 10.1111/ajd.13218
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic collision tumour of the scalp: squamous cell carcinoma and malignant melanoma

Abstract: Cutaneous collision tumours are the co-existence of two tumours of different histopathological morphologies that coincide at the same or adjacent anatomical sites. A large scalp nodule excised from a 70 year-old man revealed a collision tumour composed of cells of squamous carcinoma (SCC) and malignant melanoma. Immunohistochemistry using dual staining for melanoma and squamous cell carcinoma demonstrated an unusual pattern; nests of melanoma cells surrounded by a layer of squamous carcinoma cells. The unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…They speculate this may suggest interaction theory as the etiology of their tumor. 14 The prognosis of this rare tumor remains uncertain. 1 Many cases of SMT have been followed closely for years with no evidence of metastasis or recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…They speculate this may suggest interaction theory as the etiology of their tumor. 14 The prognosis of this rare tumor remains uncertain. 1 Many cases of SMT have been followed closely for years with no evidence of metastasis or recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Collision tumors are tumors of different tissue origins that coexist in the same tissue or organ without histological fusion ( 3 ). Collision tumors have been reported in different parts of the body, including the skin, thyroid, uterus, brain, gastrointestinal tract, and genitourinary tract ( 4 6 ). Primary renal collision tumors are rare, and only sporadic cases have been reported in the medical literature.…”
Section: Discussionmentioning
confidence: 99%
“…In Cornejo and Deng's review, they identified three collision and two combined and collision tumors comprised of SCC and melanoma 5 . In 2019, Mangkorntongsakul et al described a case report of a large and recurrent ulcerating nodule excised from the scalp of a 70‐year‐old immunosuppressed patient who had a histopathologic diagnosis of a SCC and malignant melanoma collision tumor 16 …”
Section: Collision Tumor Typesmentioning
confidence: 99%